Peningkatan Pengetahuan Warga Terhadap Pengelolaan Dan Pengolahan Sampah Di Desa Tarikolot Majalengka Jawa Barat: (Increasing Community Knowledge of Waste Management and Processing in Tarikolot Village, Majalengka, West Java) - Hamidah, Siti Nur; Anggara, Ikbal; Noval, Muhamad (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
Waste is one of the problems that never seems to be resolved, whether it comes from households, industries, or markets, which can cause environmental pollution. One of them is located in the Majalengka area, specifically in the Village/Sub-district of Tarikolot, where waste remains an unresolved problem due to the suboptimal management and processing of waste carried out by the Community. This Community Service Program aims to increase the knowledge and insight of residents regarding the importance of protecting the environment, increasing knowledge regarding the management and processing of waste, both organic, inorganic and B3, as well as knowing the recycling process for organic waste into compost, as well as inorganic waste can be used as household goods and handling of B3 waste. This research was conducted in Tarikolot Village, Majalengka, West Java. The respondents who participated were approximately 15 residents of Tarikolot. This program includes socialization and education on waste management, as well as the provision of waste bin facilities. The method used is direct observation, as well as the distribution of pre-test and post-test questionnaires to residents to measure the increase in residents' knowledge of waste and waste management and processing. Testing was conducted using the normality test with the Shapiro-Wilk and Wilcoxon Signed Ranks Tests, both of Which Were Performed using SPSS software. The results of the community service obtained show that after the socialization, there is a change in residents' knowledge of waste and management and processing, as seen based on the results of the pre-test and post-test which have increased and have an asymptotic.Sig value of 0.001, so it can be concluded that there is an increase in knowledge about waste among Tarikolot residents after the socialization. ABSTRAK Sampah menjadi salah satu permasalahan yang tidak pernah ada hentinya untuk diselesaikan, baik berasal dari rumah tangga, industri maupun pasar yang dapat menimbulkan pencemaran lingkungan. Salah satunya di daerah Majalengka tepatnya Desa/Kel. Tarikolot sampah masih menjadi masalah yang belum terselesaikan dikarenakan belum optimalnya pengelolaan dan pengolahan sampah yang  dilakukan oleh Masyarakat. Program Pengabdian Kepada Masyarakat ini bertujuan untuk meningkatkan pengetahuan dan wawasan warga terhadap pentingnya menjaga lingkungan, pengetahuan yang meningkat terhadap pengelolaan dan pengolahan sampah baik organik, anorganik maupun B3 serta mengetahui proses pendaur ulangan terhadap sampah organik menjadi pupuk kompos juga sampah anorganik bisa dimanfaatkan menjadi barang rumah tangga dan penanganan terhadap sampah B3. Penelitian ini dilakukan di Desa Tarikolot Majalengka Jawa Barat responden yang mengikuti terdapat sekitar 15 warga Tarikolot, program ini melibatkan sosialiasasi dan edukasi pengetahuan terkait pengelolaan sampah serta penyediaan fasilitas tempat sampah. Metode yang digunakan berupa  observasi langsung, juga penyebaran kuesioner pre-test dan post-test  terhadap warga untuk mengukur peningkatan pengetahuan warga terhadap sampah serta pengelolaan dan pengolahan sampah, pengujian menggunakan uji normalitas dengan Shapiro Wilk dan uji Wilcoxon Signed Ranks Test menggunakan software SPSS . Hasil pengabdian yang didapatkan menunjukkan setelah dilakukan sosialisasi bahwa terdapat perubahan pengetahuan warga terhadap sampah serta pengelolaan dan pengolahan dilihat berdasarkan hasil pre-test dan post test yang meningkat dan memiliki nilai Asymp.Sig 0.001 sehingga dapat disimpulkan bahwa terdapat peningkatan pengetahuan tentang sampah pada warga Tarikolot setelah dilakukan sosialisasi.